From Teaching of Sundanese’s Teenager Speaking Ability In Batam: Spoken Discourse Analysis: Teaching of Sundanese’s Teenager Speaking Ability in Spoken Discourse Analysis - Frangky Silitonga; Lilis Puji Astuti (Universitas Jambi, Magister Program of English Education Department, 2018)
The local language is a language that used as a characteristic of the tribe or certain people and spoken in a region within a nation. It is used as a communications tool in everyday life of the tribes who lived either on a small area, province or a wider area. The existence of local language is closely related to the existence of tribes and culture which is generated from one generation to another. Sundanese language is one of the thousands of languages that exist in Indonesia, which is become the main supporting elements of the traditions and customs of the Sundanese tribe itself. Sundanese language speaking ability is one of the important aspects in terms of preservation of Sundanese culture. By using Sundanese language in daily conversation in the family, by then it is rooted in the way of life and habits of children in the Sundanese family, in order to maintain love their ancestor language. But some Sundanese families in Batam, including the teenager, think that the Sundanese language is not necessary to be learned at this era. Some of the reasons were that because it is not been taught in school, neither a prime requirement in entering college and not considered as a priority language in entering job field, which is in demand of a foreign language beside the Indonesian language. Therefore, it slowly will disappear from the Sundanese people itself. Through her observation, she found only a few families are aware of the importance of maintaining Sundanese as prime cultural characteristic. The observations to the 11 (eleventh) teenagers have shown that only 24 % categorized has the ability in speaking Sundanese language.